Managerial equity incentive, corporate risk–taking, and corporate performance. (18th December 2014) - Zeng, Jiang–hong; Tan, Lin–ping; Chen, Xiao–hong
Based on data from the equity incentive plans of Chinese firms listed on the stock market between 2006 and 2011, this study empirically investigates the relationship between managerial equity incentive, corporate risk–taking, and corporate performance. The paper first uses the volatility of corporate earnings in order to measure the degree of corporate risk–taking, and the findings suggest that there is a significantly positive association between managerial equity incentive and corporate risk–taking. Moreover, compared to lower level staff, the risk–taking effect on managers is stronger. Additionally, the degree of corporate risk–taking of sample in China is low. Therefore an increase in the level of corporate risk–taking can considerably increase the firm's value. This paper also uses the volatility of stock returns as a proxy variable of the degree of corporate risk–taking, and the findings do not change substantially.